Hematopoietic stem cells: the power of clonal assays - Kent, David (Henry Stewart Talks, 2018)
The haematopoietic process, Spleen colony assay, Colony forming assay, Competition repopulation assay, Haematopoietic stem cell subtypes and leukemia, Index sorting experiments and the identification of a molecular overlap, Assessing somatic mutations within HSC colonies, Recapture experiments, Inferring HSC population size